2017
DOI: 10.7554/elife.25174.056
|View full text |Cite
|
Sign up to set email alerts
|

Author response: Chemical structure-guided design of dynapyrazoles, cell-permeable dynein inhibitors with a unique mode of action

Abstract: Cytoplasmic dyneins are motor proteins in the AAA+ superfamily that transport cellular cargos toward microtubule minus-ends. Recently, ciliobrevins were reported as selective cell-permeable inhibitors of cytoplasmic dyneins. As is often true for first-in-class inhibitors, the use of ciliobrevins has in part been limited by low potency. Moreover, suboptimal chemical properties, such as the potential to isomerize, have hindered efforts to improve ciliobrevins. Here, we characterized the structure of ciliobrevins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Dynapyrazole, Ciliobrevin and their Analogs In vitro and in vivo studies of ciliobrevin A and D, the two ATP-competitive ligands, have shown that they non-selectively bind to the ATP binding sites of the hexameric head of both cytoplasmic dynein 1 and dynein 2 [7,10]. Dynapyrazole A and B resulted from a chemical structure modification to produce ciliobrevin analogs with higher potency [26], for overcoming geometric isomerization complexity caused by the C8-C11 double bond in ciliobrevin. (Figure 4) Unlike the ciliobrevin analogs, which abrogate both MT-stimulated and basal ATPase activity, dynapyrazole analogs inhibit MT-stimulated ATPase activity with high potency without affecting basal ATPase activity [26].…”
Section: 1mentioning
confidence: 99%
See 4 more Smart Citations
“…Dynapyrazole, Ciliobrevin and their Analogs In vitro and in vivo studies of ciliobrevin A and D, the two ATP-competitive ligands, have shown that they non-selectively bind to the ATP binding sites of the hexameric head of both cytoplasmic dynein 1 and dynein 2 [7,10]. Dynapyrazole A and B resulted from a chemical structure modification to produce ciliobrevin analogs with higher potency [26], for overcoming geometric isomerization complexity caused by the C8-C11 double bond in ciliobrevin. (Figure 4) Unlike the ciliobrevin analogs, which abrogate both MT-stimulated and basal ATPase activity, dynapyrazole analogs inhibit MT-stimulated ATPase activity with high potency without affecting basal ATPase activity [26].…”
Section: 1mentioning
confidence: 99%
“…Dynapyrazole A and B resulted from a chemical structure modification to produce ciliobrevin analogs with higher potency [26], for overcoming geometric isomerization complexity caused by the C8-C11 double bond in ciliobrevin. (Figure 4) Unlike the ciliobrevin analogs, which abrogate both MT-stimulated and basal ATPase activity, dynapyrazole analogs inhibit MT-stimulated ATPase activity with high potency without affecting basal ATPase activity [26]. This feature resembles She1, a microtubule-associated protein (MAP) that effectively reduces MT-stimulated ATPase activity without significantly decreasing its basal activity [35].…”
Section: 1mentioning
confidence: 99%
See 3 more Smart Citations